Mapping the cellular and molecular heterogeneity of normal and malignant breast tissues and cultured cell lines. - Keller, Patricia J.; Lin, Amy F.; Arendt, Lisa M.; Klebba, Ina.; Jones, Ainsley D.; Rudnick, Jenny A.; DiMeo, Theresa A.; Gilmore, Hannah.; Jefferson, Douglas M.; Graham, Roger A.; Naber, Stephen P.; Schnitt, Stuart.; Kuperwasser, Charlotte. (2016)
Introduction: Normal and neoplastic breast tissues are comprised of heterogeneous populations of epithelial cells exhibiting various degrees of maturation and differentiation. While cultured cell lines have been derived from both normal and malignant tissues, it remains unclear to what extent they retain similar levels of differentiation and heterogeneity as that found within breast tissues.; Keywords: allophycocyanin, cytokeratin, calf serum, 4',6-diamidino-2-phenylindole, ductal carcinoma in situ, Dulbecco's modified Eagle's medium, epithelial to mesenchymal transition, epithelial cell adhesion molecule, estrogen receptor, Ham's F12 medium, fluorescence activated cell sorting, flow buffer, fetal bovine serum, fluorescein isothiocyanate, human epidermal growth factor, human mammary epithelial, human breast epithelial cell, human telomerase, mammary epithelial basal medium, mammary epithelial growth medium, phosphate buffered saline, phycoerythrin, progesterone receptor, Roswell Park Memorial Institute-1640 medium, smooth muscle actin.; Springer Open.